2016
DOI: 10.1177/0885066616646099
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity on Outcomes in a Multiethnic Cohort of Medical Intensive Care Unit Patients

Abstract: Our study supports the hypothesis that obesity is associated with decreased mortality during critical illness. However, this finding was not observed among elderly obese patients. Further studies should explore the interaction between age, obesity, and outcomes in critical illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…A total of 199,421 subjects participated in the 23 studies, which consisted of 14 prospective [ 8 , 13 , 18 29 ] and 9 retrospective cohort studies [ 9 12 , 30 35 ]. Fourteen studies were from North America [ 9 , 10 , 12 , 13 , 19 , 20 , 21 , 25 , 27 , 28 , 30 , 32 34 ], one from South America [ 31 ], five from Europe [ 8 , 18 , 22 , 23 , 24 , 29 ], and two from Australia [ 26 , 35 ]. In seven studies [ 8 , 9 , 18 , 19 , 22 , 31 , 32 ], BMIs was classified only into obese versus non-obese ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 199,421 subjects participated in the 23 studies, which consisted of 14 prospective [ 8 , 13 , 18 29 ] and 9 retrospective cohort studies [ 9 12 , 30 35 ]. Fourteen studies were from North America [ 9 , 10 , 12 , 13 , 19 , 20 , 21 , 25 , 27 , 28 , 30 , 32 34 ], one from South America [ 31 ], five from Europe [ 8 , 18 , 22 , 23 , 24 , 29 ], and two from Australia [ 26 , 35 ]. In seven studies [ 8 , 9 , 18 , 19 , 22 , 31 , 32 ], BMIs was classified only into obese versus non-obese ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of factors contribute to the association between obesity and mortality, including a series of physiological changes that result in poor stresses related to acute inflammatory and immune responses, or in many comorbidities including diabetes, cardiovascular events, respiratory diseases and cancer [ 11 ]. However, “obesity paradox” (namely, lower mortality in obese subjects) has also been reported in ICU patients in other studies [ 12 13 ]. The relationship between obesity and mortality of ICU patients thus remain largely unclear[ 14 ].…”
Section: Introductionmentioning
confidence: 86%
“…They concluded that lower BMI is associated with an increased mortality rate and worsened functional status at the time of discharge. A cohort of 699 patients also demonstrated that the obese patients have lower in-hospital mortality, though, the ndings were not witnessed among the older group of the obese patients, which suggests further studies to elaborate the possible connection between age, obesity, and fatal outcomes in intensive care units [24]. Nasraway et al showed during a cohort study in the UK that BMI > 40 was an independent cause of death in ICU-admitted surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…2 Ironically, ICU patients with obesity may actually have a greater likelihood of survival when compared with healthy body weight comparators. 3…”
mentioning
confidence: 99%
“…2 Ironically, ICU patients with obesity may actually have a greater likelihood of survival when compared with healthy body weight comparators. 3 Hypotheses exist regarding why obese patients may demonstrate improved survival in critical illness. 3,4 Appropriate medication dosing between obese and nonobese patients may contribute to observed differences in patient morbidity and mortality outcomes.…”
mentioning
confidence: 99%